Development of the CIVIC-GO Application for Civic Education with Local Wisdom Content to Enhance Students' Critical Thinking - Rahayu, Dwi Agustina; I’to, Ahmad Izzul; Ulum, Bachrul (Education and Development Research, 2026)
This study aims to develop the CIVIC-GO application based on a digital board game as a learning medium for Civic Education that integrates the local wisdom of Tulungagung, Indonesia to enhance students’ critical thinking skills. The background of this research lies in the need for more interactive, contextual, and innovative Civic Education learning aligned with 21st-century demands, since conventional methods tend to be theoretical and less engaging. The research applied the ADDIE development model consisting of needs analysis, design of the application, prototype development, implementation through small and large group trials, and evaluation of the product. The subjects were eleventh-grade high school students in Tulungagung selected using a multistage cluster sampling technique. Data were collected through observation, interviews, questionnaires, and feasibility tests conducted by media experts, material experts, and students as users. The results showed that CIVIC-GO obtained a feasibility score of 91.5% from media experts, 96% from material experts, 88.8% from small group trials, and 89% from large group trials, with an average of 91.3% categorized as very feasible. These findings indicate that CIVIC-GO is not only effective in increasing students’ motivation and engagement but also strengthens their understanding of Pancasila values through the integration of local cultural contexts. The implication of this study highlights that incorporating local wisdom into digital learning media can enrich the learning experience, foster students’ cultural identity, and provide an innovative alternative for Civic Education in the digital era.